( | 1 | + | x | + | 23 10 | ) | = | ( | 1 | + | x | ) | × | 9 5 |
Left side of the equation = | 1 | + | x | + | 23 10 |
= | 33 10 | + | x |
33 10 | + | x | = | ( | 1 | + | x | ) | × | 9 5 |
Right side of the equation = | 1 | × | 9 5 | + | x | × | 9 5 |
= | 9 5 | + | x | × | 9 5 |
33 10 | + | x | = | 9 5 | + | 9 5 | x |
x | − | 9 5 | x | = | 9 5 | − | 33 10 |
- | 4 5 | x | = | 9 5 | − | 33 10 |
- | 4 5 | x | = | - | 3 2 |
3 2 | = | 4 5 | x |
4 5 | x | = | 3 2 |
x | = | 3 2 | ÷ | 4 5 |
= | 3 2 | × | 5 4 |
x | = | 15 8 |
x | = | 1.875 |